2020
DOI: 10.1177/1534650120924128
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for a Refugee Mother With Depression and Anxiety

Abstract: This case study illustrates a short-term cognitive behavioral therapy (CBT) for a refugee single mother of a 4-year-old son to address depression and anxiety symptoms. Although she has histories of multiple trauma experiences such as sexual abuse and intimate partner violence, the client preferred to focus on current difficulties rather than trauma histories. As such, non-trauma-focused CBT utilizing psychoeducation, skill building, activity monitoring and scheduling, and cognitive restructuring is implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Of the fourteen studies included in this review, the types of studies varied considerably, representing a diverse range of research methodologies. These included pilot studies [36,37], an exploratory sequential mixed-methods study [39], a scoping review [33], a case report [40], qualitative studies [29][30][31][32]34,36], a literature review [28], a case series [38], and a systematic review [35]. When considering the sample sizes of the studies, it was observed that 2 studies had fewer than 9 participants [36,40], 3 studies had a sample size ranging from 10 to 29 participants [30,31,39], and 4 studies had a larger sample size of more than 30 participants [17,29,34,37].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the fourteen studies included in this review, the types of studies varied considerably, representing a diverse range of research methodologies. These included pilot studies [36,37], an exploratory sequential mixed-methods study [39], a scoping review [33], a case report [40], qualitative studies [29][30][31][32]34,36], a literature review [28], a case series [38], and a systematic review [35]. When considering the sample sizes of the studies, it was observed that 2 studies had fewer than 9 participants [36,40], 3 studies had a sample size ranging from 10 to 29 participants [30,31,39], and 4 studies had a larger sample size of more than 30 participants [17,29,34,37].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For one study, specific participant data were not available [32]. Four studies were either reviews or case series [28,33,35,38] Regarding the demographics of the participants, eight studies primarily focused on women [17,31,34,[36][37][38][39][40], five studies specifically included children [28][29][30]32,33], and one study involved both youths and women [35].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations